2013
DOI: 10.1002/j.2333-8504.2013.tb02313.x
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of a Nonprofit Educational Measurement Organization to Education Policy Research

Abstract: As part of its mission, Educational Testing Service (ETS) has conducted education policy research focused on promoting equal opportunity for all individuals from early childhood through adulthood. This report provides a sampler of this extensive work in three areas chosen to represent major historical foci: • Analyzing, evaluating, and informing public policy in educational governance, including school finance; teacher policy; and federal, state, and local education policy; • Examining differential access to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Many programs also require specific credentials, the most common of which is K–12 certification. Twenty-eight percent of full-time instructors in adult education programs held K–12 certification (Coley, 2008).…”
mentioning
confidence: 99%
“…Many programs also require specific credentials, the most common of which is K–12 certification. Twenty-eight percent of full-time instructors in adult education programs held K–12 certification (Coley, 2008).…”
mentioning
confidence: 99%
“…The new trainings designed under PRWORA were described as "wasteful and misguided," with unrealistically short timelines (Bok, 2004, p. 46; see also Tumlin & Zimmerman, 2003). Over the years to come, these problems would persist: An ETS Policy Note (Coley, 2008) found that on average, adult education participants spent less than 100 hours per year in class, and only one-third of them made measurable progress in that time, a figure that has not significantly improved since (U.S. Department of Education, n.d.). These findings suggest that current adult education programs are not sufficiently intensive to promote language development.…”
Section: The Shift To Labor Force Attachmentmentioning
confidence: 99%
“…These variable types were chosen because they were found to be related to the adult proficiency skills in previous studies [17][18][19][20][21] and were available for all the counties in our sample. To ensure that the values of the variables were most relevant to the PIAAC study, we obtained variables collected within the time frame of the PIAAC study.…”
Section: Identifying County and State Variablesmentioning
confidence: 99%